Chemically Induced Photoswitching of Fluorescent Probes—A General Concept for Super-Resolution Microscopy - Mike Heilemann; Peter J. Verveer; Sebastian Malkusch; Benjamin Flottmann; Justine Mondry; Piotr Liguzinski; Ulrike Endesfelder (Molecules, 2011)
We review fluorescent probes that can be photoswitched or photoactivated and are suited for single-molecule localization based super-resolution microscopy. We exploit the underlying photochemical mechanisms that allow photoswitching of many synthetic organic fluorophores in the presence of reducing agents, and study the impact of these on the photoswitching properties of various photoactivatable or photoconvertible fluorescent proteins. We have identified mEos2 as a fluorescent protein that exhibits reversible photoswitching under various imaging buffer conditions and present strategies to characterize reversible photoswitching. Finally, we discuss opportunities to combine fluorescent proteins with organic fluorophores for dual-color photoswitching microscopy.